2020
DOI: 10.1155/2020/3956070
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of Rouviere’s Sulcus and Its Association with Complication of Laparoscopic Cholecystectomy

Abstract: Background and Objective(s). Rouviere’s sulcus (RS) is an important anatomical landmark. The aim of this study was to find the distribution of anatomical characteristics of RS seen during laparoscopic cholecystectomy in the population of our part of the world and its association with complications. Methods. This is a prospective observational study involving patients of age ≥16 years who underwent laparoscopic cholecystectomy for uncomplicated gall stone at BPKIHS between May and July 2019. Result. 230 cases w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 8 publications
3
8
0
Order By: Relevance
“…These minor variations are attributed to different degrees of including the scar type of Rouviere's sulcus in these studies. The reported dimensions of Rouviere's sulcus in the current study match what was described by Singh et al 12 Visualization of Rouviere's sulcus is very common and easy during LC, Kumar et al 17 attributed this to CO2 insufflation superior illumination and excellent image quality.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These minor variations are attributed to different degrees of including the scar type of Rouviere's sulcus in these studies. The reported dimensions of Rouviere's sulcus in the current study match what was described by Singh et al 12 Visualization of Rouviere's sulcus is very common and easy during LC, Kumar et al 17 attributed this to CO2 insufflation superior illumination and excellent image quality.…”
Section: Discussionsupporting
confidence: 89%
“…Thapa et al 16 reported visualized Rouviere's sulcus in of 75% of patients, Dahmane et al 8 reported an incidence of 82%, while Peti et al 7 described an incidence of 80%. The highest reported incidence of Rouviere's sulcus (> 90% visualization rate) was reported by Singh et al 12 and Kumar et al 17 In a recent meta-analysis of 23 anatomical or laparoscopic studies, Cheruiyot et al 18 reported an overall incidence of 83%. These minor variations are attributed to different degrees of including the scar type of Rouviere's sulcus in these studies.…”
Section: Discussionmentioning
confidence: 95%
“…This highlights how the presence of RS aids in performing LCs and shortening the operative time. Similar findings were noted in a study of 230 cases conducted by Kumar A et al [ 16 ] in Nepal which showed decreased mean operative time among patients with RS visibility compared to those with non-visibility of RS (p-value <0.05).…”
Section: Discussionsupporting
confidence: 89%
“…38 (38%) cases were males while 62 (62%) were females. Kumar et al 7 found that middle-aged patients were 41.56 ± 14.27 years old and had middle-aged uncomplicated gallstones. The highest reported frequency of Rovier ridges (GOR > 90%) was reported by Kumar et al 7 who attributed this to excellent carbon dioxide production and image quality.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, Kumar et al 7 showed that the overall incidence of biliary tract lesions (BIDs) at assessment was 1 in 230, equivalent to 0.4%, and the incidence of biliary tract lesions during laparoscopic cholecystectomy indicated dissection of the abdominal cavity in the SR representatives.…”
Section: Table 1: Baseline Characteristics Of the Study Participantsmentioning
confidence: 99%